Comparative Linguistic and Pragmatic Analysis of News Translation in English and Uzbek Media (Diversity Research: Journal of Analysis and Trends, 2026)
The present study offers an expanded comparative-linguistic and pragmatic investigation of media text translation between English and Uzbek, with particular emphasis on discourse strategies, cognitive transformations, ideological framing, and cross-cultural adaptation mechanisms. In the contemporary digital communication ecosystem, media discourse functions not merely as an informational vehicle but as a powerful instrument of agendasetting, socio-political framing, and identity construction. Translation in this domain therefore transcends lexical equivalence and becomes a multidimensional communicative act shaped by linguistic structure, pragmatic intention, and cultural cognition